A Review on Alternative Refrigerants: Advancements in Eco-friendly Refrigerants and Cooler System Performance (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Over the past decade, major research was carried out on refrigeration cycles and systems with a specific focus on the substitution of coolant such as R134a by coolant such as hydrocarbons with marginal GWP (Global Warming Potential). In addition to the usage of eco-friendly refrigerants, strategies for improving the performance of the coolersystem have been developed that will also help reduce emissions of GHG (Green House Gases). This paper examines attempts to substitute environmentally harmful HFCs (hydroflurocarbons).